Tanggung jawab Indonesia Akibat Pencemaran Kabut Asap Lintas Batas - Avrieska Putri Irani (JURNAL HUKUM DE'RECHTSSTAAT, 2021)
The responsibility of countries in the ASEAN agreement regarding transboundary haze pollution is only regulated in general terms, but in the agreement there is no specific stipulation regarding the state's responsibility which causes the emergence of transboundary haze in the Southeast Asia region. Therefore it is important to discuss how the concept of implementing the state responsibility. This research is a juridical-normative research with a statute approach and a conceptual approach based on data obtained from literature studies and various facts in the field from various media. The urgency of regulating state responsibility which causes transboundary haze is important as a manifestation of respect for the sovereignty of other countries in the Southeast Asia region. Although Indonesia as a country cannot be said rigidly as the one that pollutes transboundary haze, efforts to account for Indonesia as a country can be carried out by applying the principle of imputability. Meanwhile, Indonesia as a country can also fulfill its responsibility for pollution without prosecution in the form compensation and apology. In addition, Indonesia can take action against those who should be responsible for forest and land fires as a form of its territorial jurisdiction.